The role of olefin geometry in the activity of hydrocarbon stapled peptides targeting eukaryotic translation initiation factor 4E (eIF4E). Issue 26 (19th June 2019) - Song, James M.; Gallagher, Erin E.; Menon, Arya; Mishra, Lauren D.; Garner, Amanda L.
Abstract : Ring-closing metathesis of monosubstituted alkenyl amino acids leads to stapled peptides with differing olefin geometry and biological activity. Abstract : Hydrocarbon stapled (HCS) peptides are a class of cross-linked α-helix mimetics. The technology relies on the use of α, α′-disubstituted alkenyl amino acids, which fully contrain the helical region to typically yield peptides with enhanced structural ordering and biological activity. Recently, monosubstituted alkenyl amino acids were disclosed for peptide stapling; however, the impact that this tether has on HCS peptide structure and activity has not yet been fully explored. By applying this HCS to the disordered peptide eIF4E-binding protein 1 (4E-BP1), we discovered that this type of tethering has a dramatic effect on olefin geometry and activity of the resultant stapled peptides, where the putative trans isomer was found to exhibit enhanced in vitro and cellular inhibitory activity against eIF4E protein–protein interactions. We further demonstrated that the metathesis catalyst used for ring-closing metathesis can influence monosubstituted HCS peptide activity, presumably through alteration of the cis / trans olefin ratio. This study represents one of the first in-depth analyses of olefin isomers of a stapled peptide and highlights an additional feature for medicinal chemistry optimization of this class of peptide-based probes.